8. Inefektivitas Peran ASEAN Capital Market Forum terhadap Pembangunan Sistem Keamanan Pasar dalam Persiapan Integrasi Pasar Modal ASEAN - Alifah Nurul Izzati; Tri Cahyo Utomo; Ika Riswanti Putranti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
The process to build integrated ASEAN capital market finds many obstacles because of the different national interest among its member countries. ASEAN Capital Market Forum (ACMF) as the forum that specifically created to handle this integration can not even have effective role to urges this ASEAN integrated capital market. This research conducted to examine the cause of this obstructed process that aimed to build the member state’s welfare, academically managed to explain this problem from International Relation’s spectacles. Referring to liberal intergovernmentalism by Andrew Moravcsik, this obstacles may happen because of coutry as main actor on international relations that rationally acts, tend to choose the most beneficial option that can maximize the gain of their interest. Because of this research uses qualitative data from literature review and interview, so this research can be qualified as qualitative research. The result of this research is that the difference of national interest based on economic disparities strongly occur, where high and upper middle income countries will support this initiative but in the other hand the low and lower middle income countries still prefer FDI which is more productive.